A cruzada como política senhorial : discursos, relações de poder e disputas pela autoridade em torno de Raimundo de Saint-Gilles (1041-1099) - Oliveira, André Marinho de (2015)
This work propounds to analyze the Crusades by the politic vision of Raymond of Toulouse. This temporal marks follow the historical subject, starting with born of Raymond IV (1041) and end up to of the First Crusade (1099); account his lifetime including both the conquer of title of earl of Toulouse and his participation as crusade. For we could relate about this points, we established a common point for most of lords and their domains formations. While we make the analyses of sources, we could methodological measure on the politic behavior of Raymond. In the midst of so many political apparatus, we propose to find the use of the spiritualized in the justification of the conquest, the discussion of authority and power for the Crusades, as well as the multiplicity of policies established by the great diversity of lords of which attended the event. The bibliography to encompass all these issues, ranging from classical texts with more recent discussions: report the nodal points of landlord range from discussions of Marc Bloch and George Duby and include the recent one Thomas N. Bisson and Dominique Barthelemy. Steven Runciman and Christopher Tyerman are also report the details with Raymond d’Aguilers, the chronicler of the count, and Foucher de Chartres, both members of the crusades. These Sources and some others are in the compilation work of August C. Krey whose elucidative notes are included in this work, despite inside the Krey work.